For Worse? Financial Hardships and Intra-Household Resource Allocation among Australian Couples - Ferdi Botha; David C. Ribar (Institute of Labor Economics (IZA), 2020)
This paper considers the association between intra-household resource allocation and couple financial hardships in Australia. It develops and estimates a collective household model of expenditures on individual-specific necessities and hardship reporting where each partner has a distinct utility function and household decisions are assumed to be Pareto efficient. Using data from the 16th wave of the Household, Income, and Labour Dynamics in Australia Survey with unique questions on individual financial hardships, this paper addresses disadvantage brought about by financial hardships that may be shaped in part by the distributions of preferences and bargaining power within households. Wives report more hardships than husbands. Estimates indicate that wives have weaker preferences than husbands for expenditures on necessary goods for themselves, but there is no evidence of differences in bargaining power. Estimates further indicate that hardships increase with the number of children and each spouse's disability status and decrease with their ages and subjective financial capabilities.
Keywords: D12; D13; I31; 330; financial hardship; intra-household allocation; couples; Australia